3D-CT reconstruction for pedicle outer width assessment in patients with thoracolumbar spine fractures: a comparative analysis between age groups <60 years and ≥60 years - He, Qiang; Yan, Yifeng; Mei, Jie; Xie, Chengxin; Sun, Xin (Frontiers in Surgery, 2024)
Objective: This study aims to compare the utilization of 3D-CT reconstruction in measuring pedicle outer width (POW) between younger/middle-aged patients (<60 years) and older patients (≥60 years) with thoracolumbar spine fractures (TSF). Methods: We conducted a retrospective study from January 2021 to December 2022, involving a total of 108 patients with TSF. The study population consisted of 62 patients aged ≥60 years (observation group) and 46 patients aged <60 years (control group). We compared the POW on both the right and left sides of the thoracolumbar spine between the two groups. Additionally, we analyzed the POW by gender within each group and calculated the incidence of patients falling below the critical values for arch root puncture (5mm) and arch root nailing (7mm) in both groups. Results: There were no statistically significant differences observed in the POW between the two groups on both the left and right sides of each corresponding vertebra (P>0.05). In the observation group, both male and female patients had significantly smaller POW compared to the control group (P<0.05). However, no significant difference in POW was observed between the same-sex groups in the L4 to L5 vertebrae (P>0.05). In the observation group, the POW was less than 5mm in 9.33% (81/868) of cases and less than 7mm in 49.88% (433/868) of cases, primarily observed from T11 to L3. In the control group, 4.81% (31/644) of cases had a POW of less than 5mm, and 13.81% (88/644) had a POW of less than 7mm. Conclusion: Utilizing preoperative 3D-CT reconstruction to measure POW in patients with TSF not only facilitates the assessment of surgical feasibility but also aids in surgical pathway planning, thus potentially reducing the incidence of postoperative complications.